2023
DOI: 10.1111/febs.16738
|View full text |Cite
|
Sign up to set email alerts
|

Lipids uniquely alter the secondary structure and toxicity of amyloid beta 1–42 aggregates

Abstract: Abrupt aggregation of amyloid β1‐42 (Aβ) peptide is a hallmark of Alzheimer's disease (AD), a severe pathology that affects more than 44 million people worldwide. A growing body of evidence suggests that lipids can uniquely alter rates of Aβ1‐42 aggregation. However, it remains unclear whether lipids only alter rates of protein aggregation or also uniquely modify the secondary structure and toxicity of Aβ1‐42 oligomers and fibrils. In this study, we investigated the effect of phosphatidylcholine (PC), cardioli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 80 publications
(115 reference statements)
5
42
0
Order By: Relevance
“…One can expect that the presence of lipids on the surface of oligomers and fibrils drastically changed their interactions with the cell membranes, which ultimately lead to the observed differences in the oligomers' and fibrils' toxicity. At the same time, Zhaliazka and co‐workers recently demonstrated a direct relationship between the amount of β‐sheet and toxicity of amyloid β 1‐42 aggregates (Zhaliazka, Matveyenka, & Kurouski, 2023a). Thus, one can expect that differences in the secondary structure of amyloid aggregates determine their toxicity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…One can expect that the presence of lipids on the surface of oligomers and fibrils drastically changed their interactions with the cell membranes, which ultimately lead to the observed differences in the oligomers' and fibrils' toxicity. At the same time, Zhaliazka and co‐workers recently demonstrated a direct relationship between the amount of β‐sheet and toxicity of amyloid β 1‐42 aggregates (Zhaliazka, Matveyenka, & Kurouski, 2023a). Thus, one can expect that differences in the secondary structure of amyloid aggregates determine their toxicity.…”
Section: Discussionmentioning
confidence: 97%
“…It was also found that Aβ exhibited substantially higher affinity to cholesterol compared to phospholipids, and FAs (Avdulov et al, 1997). Our own experimental results showed that lipids present in the structure of Aβ oligomers formed in their presence (Zhaliazka & Kurouski, 2023). We infer that the presence of lipids drastically changes the hydrophobic properties of oligomer surfaces facilitating their property to permeabilize plasma membranes (Matveyenka et al, 2023; Matveyenka, Rizevsky, & Kurouski, 2022a; Matveyenka, Rizevsky, & Kurouski, 2022b; Matveyenka, Zhaliazka, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 , 19 , 32 35 Thus, AFM-IR can be used to determine the chemical structure of individual protein aggregates. 26 31 , 33 37 Using AFM-IR, Rizevsky and co-workers also found that both PC and CL were found to be present in insulin oligomers that were grown in the presence of these phospholipids. 18 Independently, Matveyenka and co-workers demonstrated that the degree of saturation of FAs of both PC and CL plays an important role in insulin aggregation.…”
Section: Introductionmentioning
confidence: 97%
“…Using nanoinfrared spectroscopy, also known as atomic force microscopy infrared (AFM-IR) spectroscopy, the researchers demonstrated that insulin strongly interacts with both phosphatidylcholine (PC) and cardiolipin (CL). In AFM-IR, a metallized scanning probe is placed on the sample of interest. Next, the sample is illuminated by pulsed tunable IR laser, which induces thermal expansions in the sample. These expansions are recorded by the probe and converted into IR spectra. ,, Thus, AFM-IR can be used to determine the chemical structure of individual protein aggregates. , Using AFM-IR, Rizevsky and co-workers also found that both PC and CL were found to be present in insulin oligomers that were grown in the presence of these phospholipids . Independently, Matveyenka and co-workers demonstrated that the degree of saturation of FAs of both PC and CL plays an important role in insulin aggregation .…”
Section: Introductionmentioning
confidence: 99%